Taqlid Digital Dalam Fenomena Politik Identitas Berbasis Keagamaan - Dyah Erie Shinta Putri; Avivah Firisqi Leksono (Universitas Sebelas Maret, 2025)
Islamic law is always experiencing development as a necessity for change, one of the developments is taqlid. Entering the digital era, the concept of taqlid has undergone a major transformation, giving birth to the digital taqlid phenomenon. To read the phenomenon of digital taqlid in the Ahok case, a religious phenomenology analysis knife is used to see that a person's consciousness always leads to a certain meaning and can be known from a first-person perspective. This particular meaning is related to the symbol of religious blasphemy as a narrative. This research uses normative legal research with the type of library research. Data collection techniques using primary legal materials in the form of books and related journal articles. The data analysis method used is content analysis (content analysis). The results of the research state that taqlid is doing good deeds by following other people's words or opinions which have no proof value and not knowing the causes or arguments and proofs of the opinions one follows. In the context of digital taqlid, the phenomenon of Ahok's case can be called digital taqlid that extracts knowledge from the path of ignorance. People tend to immediately receive information directly without exploring the ins and outs. Therefore, at least someone understands something, at least someone is equipped with high literacy to read the reality of what is happening so that what they follow does not make them go astray or make a wrong move.